(untitled) (Asian Journal of Pharmaceutics (AJP), 2016)
Introduction: Natural products derived from plants kingdom play a vital part in preventing or treating various diseases or disorders in humans. Hyperlipidemia is one of the major pathological factors of cardiovascular diseases and diabetes mellitus. On the other hand, Leucas aspera Linn., belonging to the family Lamiaceae, was found to possess many pharmacological activities such as anti-inflammatory, antibacterial, and antiplasmodial activities along with cytotoxic effects. Materials and Methods: The present study is an attempt to investigate its antihyperlipidemic activity by in vivo animal model. Hyperlipidemia model can be induced by administered with dexamethasone in rats with significant increase in serum cholesterol and triglyceride (TG) levels along with increase in the atherogenic index. Results: The ethanolic extract of leaves of L. aspera Linn. (200 and 400 mg/kg) treatment has shown significant inhibition against dexamethasone-induced hyperlipidemia in rats by maintaining the serum levels of cholesterol, TGs and near to the normal levels